2015
DOI: 10.1002/bio.3010
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of human serum albumin with novel imidazole derivatives studied by spectroscopy and molecular docking

Abstract: This study was a detailed characterization of the interaction of a series of imidazole derivatives with a model transport protein, human serum albumin (HSA). Fluorescence and time-resolved fluorescence results showed the existence of a static quenching mode for the HSA-imidazole derivative interaction. The binding constant at 296 K was in the order of 10(4) M(-1), showing high affinity between the imidazole derivatives and HSA. A site marker competition study combined with molecular docking revealed that the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…Fluorescence quenching based on the interaction between substances can be divided into static quenching and dynamic quenching. When studying the protein–polyphenol interaction, Stern–Volmer equation can be used to determine the quenching type (Yue et al., ): F0F=1+KnormalqτιQ=1+K sv Qwhere F 0 and F are the fluorescence intensities of the pepsin solution when OeB is not added and added respectively; [ Q ] is the total concentration of OeB, K q is the quenching rate constant, K sv is the Stern–Volmer quenching constant, K q = K sv /τ 0 , the maximum scattering collision quenching constant of various fluorescent quenchers on biomacromolecules is about 2.0 × 10 10 L/(mol•s); τ 0 is the lifetime of fluorescence in the absence of quencher, and the average lifetime of fluorescence ( τ 0 ) is about 10 −8 s. According to Stern–Volmer equation, with [ Q ] as independent variable and F 0 / F as dependent variable, Figure B is obtained by linear fitting, and quenching parameters can be calculated, as shown in Table . The K q values of OeB–pepsin are much larger than 2.0 × 10 10 L/(mol·s).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluorescence quenching based on the interaction between substances can be divided into static quenching and dynamic quenching. When studying the protein–polyphenol interaction, Stern–Volmer equation can be used to determine the quenching type (Yue et al., ): F0F=1+KnormalqτιQ=1+K sv Qwhere F 0 and F are the fluorescence intensities of the pepsin solution when OeB is not added and added respectively; [ Q ] is the total concentration of OeB, K q is the quenching rate constant, K sv is the Stern–Volmer quenching constant, K q = K sv /τ 0 , the maximum scattering collision quenching constant of various fluorescent quenchers on biomacromolecules is about 2.0 × 10 10 L/(mol•s); τ 0 is the lifetime of fluorescence in the absence of quencher, and the average lifetime of fluorescence ( τ 0 ) is about 10 −8 s. According to Stern–Volmer equation, with [ Q ] as independent variable and F 0 / F as dependent variable, Figure B is obtained by linear fitting, and quenching parameters can be calculated, as shown in Table . The K q values of OeB–pepsin are much larger than 2.0 × 10 10 L/(mol·s).…”
Section: Resultsmentioning
confidence: 99%
“…The UV‐visible spectrum at 37 °C was recorded using a Shimadzu UV‐2450 spectrophotometer (Shimadzu, Japan). The fluorescence intensity obtained at different OeB concentrations is corrected by using the following equation for the internal filter effect (Yue et al., ): F cor =F obs 10A ex +A em 2where A ex and A em are the absorbance at excitation (280 nm) and emission wavelengths (338 nm), F obs and F cor are measured and corrected fluorescence intensities, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence spectra were recorded in the wavelength range of 290–450 nm in a 1.0 cm quartz cell (λ ex /λ em = 280/338 nm, slit width 5.0/5.0 nm). The fluorescence intensity was corrected by using eqn (2) to overcome the inner filtering effect (Yue et al ., ). Fitaliccor=Fitalicobs×eAex+Aem2where A ex and A em are the absorbances at the excitation and emission wavelengths, respectively.…”
Section: Methodsmentioning
confidence: 97%
“…The fluorescence characteristics of serum albumins provide critical information for the study of their interactions with several molecules of clinical interest (4,5). Many biochemical studies have reported on the interactions of small molecules with HSA using fluorescence quenching such as derivatives of coumarin (6), acridine (7), phenanthridine (8) and imidazole (9,10); sinomenine (11) phthalate plasticizers (12), helicid (13), and a benzimidazole derivative (14) etc. HSA is a globular protein consisting of a single polypeptide chain with 585 amino acids, and contains three structurally homologous domains (I, II and III).…”
Section: Introductionmentioning
confidence: 99%